Depression among adolescents living in orphanages in central Aceh district, Indonesia - Ajarni Ajarni; Radhiah Zakaria; Meutia Zahara; Asnawi Abdullah; Maidar Maidar (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Mental health is an important aspect of human life. Traumatic experiences in childhood are associated with increased mental health morbidity. Factors such as lack of parental support, low self-esteem, and social difficulties play a role in increasing the risk of risky behavior in adolescents. Purpose: To determine the determinant factors that influence the incidence of depression in adolescents living in orphanages in Central Aceh Regency. Method: Used a Cross Sectional design in four orphanages in August 2023. The sample consisted of 302 adolescents aged 8-18 years, selected by purposive sampling. The analysis used logistic regression with 95% confidence. Results: A total of 121 respondents (40.07%) experienced depression. Related factors were education, region of origin, family visits, social support, and social discrimination. Social support was the most dominant factor (AOR=5.64; p=0.000). Conclusion: Social support plays a major role in preventing depression in adolescents in orphanages, so interventions that increase social support need to be prioritized. Suggestion: Explore other psychosocial factors such as quality of relationship with caregivers, trauma experiences, and adolescent coping strategies.